Being and worth - Collier, Andrew, 1944-2014 (Routledge, 1999)
"Being and Worth extends recent depth-realist philosophy to the question of values. It argues that beings both in the natural and human worlds have worth in themselves, whether we recognise it or not. It defends this view through an account of the human mind as essentially concerned with what is independent of it." "The book builds on Roy Bhaskar's proof that facts can entail values, and it aims to repeat in the realm of ethics his argument that experiment and change in science show that there is a depth-dimension of real structures in nature and society. This it does by a partial defence and immanent critique of Spinoza's philosophy of mind and ethics."--Jacket